AB0464 The Efficacy and Safety of Iguratimod in Rheumatoid Arthritis Patients with Chronic Renal Failure. (10th June 2014) - Kume, K.; Amano, K.; Yamada, S.; Kanazawa, T.; Hatta, K.
Abstract : Background: Methotrexate (MTX) is the first line drug in rheumatoid arthritis (RA) patients. However MTX couldn't be treated in RA patients due to renal failure. Iguratimod is a newly-developed disease-modifying antirheumatic drug (DMARD) that was approved in Japan in 2012. Iguratimod is not related with renal metastasis, and it is used for RA patients with chronic renal failure. Objectives: To evaluate the efficacy and safety of Iguratimod in RA patients with chronic renal failure in a cohort study design. Methods: RA patient (2010 ACR/EULAR criteria) with chronic renal failure (estimate GFR<50) were eligible if they had active disease despite treatment. Consecutive 21 patients with moderate to severe active RA patients (DAS28>3.2) were received Iguratimod plus previous DMARDs. Disease activity and renal function were assessed at baseline and 52 weeks follow-up. We compared disease activity and renal function at baseline with 52 weeks. Results: 18 patients were completed this study. DAS 28 was significantly improved from baseline to 52 weeks (baseline: 5.33±1.44, 52 weeks: 3.45±1.65, p<0.05). There were no patients that eGFR were worsened due to Iguratimod (baseline 65.4±12.2, 52 weeks 64.5±13.4, p=0.76). Conclusions: Iguratimod was effective and safety in RA patients with chronic renal failure. Iguratimod could be used for RA patients with chronic renal failure. Acknowledgements: We thank Dr Hiroshi Komori, Hiroyuki Ohta, and Naohiko Matsumoto at department of internal medicine, Hiroshima Clinic for checking data. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1040